2020
DOI: 10.1186/s12883-020-01798-x
|View full text |Cite
|
Sign up to set email alerts
|

Failure to thrive - an overlooked manifestation of KMT2B-related dystonia: a case presentation

Abstract: Background: KMT2B-related dystonia is a recently described form of childhood onset dystonia that may improve with deep brain stimulation. Prior reports have focused on neurologic features including prominent bulbar involvement without detailing general health consequences that may result from orolingual dysfunction. We describe a family with novel KMT2B mutation with several members with failure to thrive to highlight this nonneurologic, but consequential impact of mutation in this gene. Case presentation: We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In fact, Cif et al, 2020 identified nine patients harboring pathogenic KMT2B variants, in whom no dystonic features developed at time of assessment (median age 11.8 years with a range from 2.2–57.0 years). Additional features related to KMT2B variants have been documented such as failure to thrive, renal involvement, retinal dystrophy, oculomotor abnormalities like impaired saccades and strabismus, skin changes like cutis aplasia, and additional psychiatric comorbidities such as ADHD, anxiety, depression, and obsessive-compulsive disorder ( Abela and Kurian, 2018 ; Ng et al, 2020 ). There have also been reports of myoclonus, seizures, spasticity, and sensorineural hearing loss ( Meyer et al, 2017 ; Abela and Kurian, 2018 ; Zech et al, 2019 ; Owczarzak et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Cif et al, 2020 identified nine patients harboring pathogenic KMT2B variants, in whom no dystonic features developed at time of assessment (median age 11.8 years with a range from 2.2–57.0 years). Additional features related to KMT2B variants have been documented such as failure to thrive, renal involvement, retinal dystrophy, oculomotor abnormalities like impaired saccades and strabismus, skin changes like cutis aplasia, and additional psychiatric comorbidities such as ADHD, anxiety, depression, and obsessive-compulsive disorder ( Abela and Kurian, 2018 ; Ng et al, 2020 ). There have also been reports of myoclonus, seizures, spasticity, and sensorineural hearing loss ( Meyer et al, 2017 ; Abela and Kurian, 2018 ; Zech et al, 2019 ; Owczarzak et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since that publication, there has been a further expansion of the literature with 18 scientific papers, comprising 60 additional patients with pathogenic, likely pathogenic or VUSs. 5,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] A single report of a synonymous variant leading to the generation of a premature stop codon resulting in early-onset dystonia has also been published. 8 In contrast to the world literature, the most common mutations www.e-jmd.org 291 in the KMT2B gene in our study cohort were missense mutations (n = 5), followed by two PTVs (Table 2, Supplementary Tables 3 and 4 in the online-only Data Supplement).…”
Section: Discussionmentioning
confidence: 99%
“…Only one other family has been described with KMT2Brelated dystonia due to this exact mutation. 4 PolyPhen and SIFT analysis predict this variant's pathogenicity. This allele is not found in the gnomAD database.…”
mentioning
confidence: 99%